PENGARUH MODAL KERJA, TENAGA KERJA, DAN LUAS LAHAN TERHADAP PRODUKSI PETANI MELON DI DESA KLOTOK KECAMATAN PLUMPANG KABUPATEN TUBAN - Siti Nur Amalia; Joko Priyono (CV. Denasya Smart Publisher, 2024)
This research aims to determine the influence of Working Capital, Labor and Land Area on Melon Farmers' Production in Klotok Village Plumpang District, Tuban Regency. This research design uses ex post facto research method. The data used is quantitative data. The analytical method used is the ratio test, the analytical tool used in this research is SPSS 26. The results of this research show Capital Partial work has a significant effect on the production of melon farmers in Klotok Village, Plumpang District, Tuban Regency, partial employment has a significant effect on the production of melon farmers in Klotok Village, District Tuban Regency Plumpang, and Land Area partially have a significant effect on the Production of Melon Farmers in Klotok Village, Plumpang District, Regency Tuban. And simultaneously working capital, labor and land area has a significant effect on the production of melon farmers in Klotok Village, District Plumpang, Tuban Regency.